Clinical feasibility and benefits of a tapered, sand-blasted, and acid-etched surfaced tissue-level dental implant - Buyanbileg Sodnom-Ish; Mi Young Eo; Truc Thi Hoang Nguyen; Myung-Joo Kim; Soung Min Kim (SpringerOpen, 2020)
Abstract Background It has been 50 years since Brånemark first introduced the concept of osseointegration. Since then, numerous ongoing research, developments, and optimization of implant properties have been conducted. Despite the high survival and success rates of dental implants, failures still occur in a small number of patients that are being rehabilitated by implants. The purpose of this study was to evaluate the survival and success rate of the Stella® implants that incorporate sand-blasted and acid-etched (S&E) surface treatment and tapered body design to confirm their clinical feasibility and benefits after placement. Methods We reviewed 61 partially and fully edentulous patients who underwent a tapered, S&E surfaced tissue-level implant placement between May 2013 and February 2016 in the Department of Oral and Maxillofacial Surgery in the Seoul National University Dental Hospital. Patient characteristics and treatment results were collected, and records of dental implants were analyzed clinically and radiologically. Results A total of 105 implant fixtures were placed in these patients. The mean age at the time of the surgery was 63.7 years with a range of 31 to 88 years. In total, 4.0-mm and 4.5-mm diameter implants were the most frequently used dental implants (40%, 49%) in this study. Implants 8.5 mm in length were predominantly used (60%). Seventy dental implants were placed in the mandible (70%), and only one dental implant was placed in the maxillary anterior region. At the end of the 5-year observation period, the success rate of the Stella® implants was 98.1%. Among the 105 implants placed, 2 were considered to be failures. Summarizing the clinical and radiographic results, the remaining 103 implants were considered successfully integrated. Conclusion The overall success rate was 98.1%. The tapered, S&E surfaced tissue-level implant system exhibited great performance in a variety of clinical situations including failed implant sites that enabled predictable and successful treatment outcomes. The effectives of a tapered design of tissue level, not a parallel design, are shown in this clinical report.